Gamification to support crowdsourcing and participatory mapping for signaling and spatialization of Covid-19 transmission predictors - Arouca, Murilo Guerreiro; Ribeiro, Ailton; Amorim, Ana Maria; Neves, Isa Beatriz; Vieira, Vaninha; Barreto, Marcos; Costa, Federico; Brito, Ricardo (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2024: Anais do XIX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2024.238059, 2024)
The active involvement of the population in health initiatives is crucial to combating Covid-19, especially in vulnerable urban communities. In these areas, the absence of detailed geographic data is a challenge for effective spatial interventions. This study proposes a solution that implements a gamification design model to support participation in disease combat initiatives through participatory mapping and crowdsourcing approaches. The UTAUT was employed to identify conditions influencing the solution's acceptance. A study involving 20 young individuals from a suburban community in Brazil demonstrated that "effort expectancy" and "social influence" significantly impact the behavioral intention to use the platform.